MO883FATIGUE IS THE PREDOMINANT PATIENT-REPORTED OUTCOME MEASURE IN HEMODIALYSIS PATIENTS: RESULTS OF A MULTICENTER CROSS-SECTIONAL EPROMS STUDY. (29th May 2021) - Guerraoui, Abdallah; Kolko-Labadens, Anne; Prezelin-Reydit, Mathilde; Chauveau, Philippe; Lasseur, Catherine; Lino-Daniel, Marie; Haesebaert, Julie; Cailette-beaudoin, Agnes
Abstract: Background and Aims: End Stage renal disease (ESRD) and hemodialysis are associated with a decrease in quality of life (QOL). Self-reported QOL symptoms are not always prioritized by the medical team, potentially leading to conflicting priorities with patients. Electronic patient-reported outcome measures (ePROMs) allow physicians to better describe these symptoms. The objective was to describe the prevalence of symptoms self-reported by HD patients. Method: A multicenter cross-sectional study was conducted in three HD centers. Patients were included if they were 18 years old or over and treated with HD for at least three months in a center. Data were collected by the patient via a self-administered ePROMs questionnaire. Data included patient characteristics, post-dialysis fatigue and intensity, recovery time after a session, perceived stress, impaired sleep the day before the dialysis session, current state of health, and the one-year change. Results: In total, we included 173 patients with a mean age of 66.2 years, a mean ± SD hemodialysis duration of 48.9 ± 58.02 months, mainly treated in self-dialysis unit (67%) and having at least one comorbidity (72.5%). The prevalence of fatigue was 72.1% [IC 95% 64.7% to 78.7%] with a mean severity score of 5.84± 2.12. 66.4% had a high level of stress (level B or C). Recovery time was more than 6 hours for 24.9% of patients and 78 % declared they had a better or unchanged health status than the previous year. The self-perceived health status of patients was 6.2± 2.12 and 77.5% [IC 95% 70.5% to 83.5%] of patients stated that they had not a worsened health status than the year before. No statistical differences were observed between centers for the PROMS. Despite significant differences in patient characteristics from the three centers including age, comorbidities or type of dialysis, no differences were found on the prevalence of the various PROMs, in favor of internally Conclusion: Fatigue and stress were the main symptoms reported by HD patients. There was no association between symptoms reported and comorbidities clinical results of patients. The patient's care teams should better consider these symptoms.